2018
DOI: 10.1016/j.ultsonch.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation at filler metal/substrate interface during ultrasonic-assisted soldering. Part I: Cavitation characteristics

Abstract: The cavitation characteristics at filler metal/substrate interface during ultrasonic-assisted soldering were first recorded by high-speed photography in this work. Two kinds of bubbles, steady cavitation bubbles and transient cavitation bubbles were observed. Steady cavitation bubbles did not collapse within one acoustic period and could last longer than 50 acoustic periods. Transient cavitation bubbles formed and collapsed within one acoustic period. The cavitation process was divided into two stages based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…For comparison, the butt joint of ZrO 2 ceramic substrates has also been soldered using Sn–4Al–0.7Cu solder at 350°C without the assistance of ultrasonic waves, the solder did not wet and no Al 2 O 3 interphase layer formed on the surface of ZrO 2 ceramic at all, furthermore, according to the study of Kaplan et al, the processing temperature for the occurrence of the oxidation reaction at the liquid‐aluminum/sapphire‐nanorod should be as high as 700‐800°C, which indicate that the sonochemically activating effects of ultrasound was the necessary condition for the occurrence of the interfacial oxidation reaction at the low soldering temperature of 350°C in this study. Previous studies have reported that the propagation of ultrasonic waves in a liquid solder could generate acoustic cavitation phenomena, which is the formation, growth and rapid implosive collapse of a vapor‐filled microbubble . Rapid bubble implosion can induce tiny hot spots with the localized extreme temperature and pressure estimated to be 5000 K and 0.1 GPa, respectively .…”
Section: Energy Dispersive Spectrometer Analysis (Wt%) Of Various Posmentioning
confidence: 99%
“…For comparison, the butt joint of ZrO 2 ceramic substrates has also been soldered using Sn–4Al–0.7Cu solder at 350°C without the assistance of ultrasonic waves, the solder did not wet and no Al 2 O 3 interphase layer formed on the surface of ZrO 2 ceramic at all, furthermore, according to the study of Kaplan et al, the processing temperature for the occurrence of the oxidation reaction at the liquid‐aluminum/sapphire‐nanorod should be as high as 700‐800°C, which indicate that the sonochemically activating effects of ultrasound was the necessary condition for the occurrence of the interfacial oxidation reaction at the low soldering temperature of 350°C in this study. Previous studies have reported that the propagation of ultrasonic waves in a liquid solder could generate acoustic cavitation phenomena, which is the formation, growth and rapid implosive collapse of a vapor‐filled microbubble . Rapid bubble implosion can induce tiny hot spots with the localized extreme temperature and pressure estimated to be 5000 K and 0.1 GPa, respectively .…”
Section: Energy Dispersive Spectrometer Analysis (Wt%) Of Various Posmentioning
confidence: 99%
“…As the cavitation threshold of the liquids is 0.3–0.6 × 10 5 Pa, which is much lower than the acoustic pressure caused by USV, a large number of cavitation bubbles are generated in the eutectic and the MgO layers are effectively removed by these bubbles [61]. In addition, due to the numerous bubbles that are ceaselessly formed and collapsed, the dissolution activation energy is decreased and the dissolution rate at the interface is accelerated remarkably [59,62]. Therefore, both the diffusion and the dissolution between the Ni foil and the Mg BM can be accelerated by USV and the Ni foil will be consumed within 27 s, which is shown in Figure 9e.…”
Section: Discussionmentioning
confidence: 99%
“…12 and 13 depict) would not be altered by the input power level (Refs. 43,44). Therefore, the vibration intensity on pure Al was the weakest under Mode I and the strongest under Mode III.…”
Section: Influence Of Ultrasonic Powermentioning
confidence: 95%